Religion and the Everyday Life of Manichaeans in Kellis: Beyond Light and Darkness - Brand, Mattias (Brill, 2022)
Religion is never simply there. In Religion and the Everyday Life of Manichaeans in Kellis, Mattias Brand shows where and when ordinary individuals and families in Egypt practiced a Manichaean way of life. Rather than portraying this ancient religion as a well-structured, totalizing community, the fourth-century papyri sketch a dynamic image of lived religious practice, with all the contradictions, fuzzy boundaries, and limitations of everyday life. Following these microhistorical insights, this book demonstrates how family life, gift-giving, death rituals, communal gatherings, and book writing are connected to our larger academic debates about religious change in late antiquity